A critical review of the effect of factory closures on health. Issue 1 (January 1991) - Morris, J K; Cook, D G
Abstract : The dramatic rise in unemployment in the 1970s and 1980s has led to an increase in research into the possible effects of unemployment on health. Studies of the effects of job loss are difficult to interpret because of the difficulty in ruling out selection effects–for example, the least fit may be more likely to be made redundant. The study of factory closures is appealing since all employees are made redundant and all the studies of factory closure recorded in the Index Medicus since 1980 are reviewed. None of the studies fulfil all the criteria for an ideal study, and most fail on several counts. The small sample sizes are often unavoidable, but the lack of awareness of possible selection effects often results in a biased control group of only those people who are economically active. Also, the short duration of follow up restricts the detection of possible long term effects on health. Thus the conclusions that can be drawn about the health effects of factory closures are limited. Whereas there is evidence of short term effects on mental health and of increased use of primary health care, no long term effects have been studied and objective data on physical health are almost non-existent.